2020
DOI: 10.1177/0145721720965464
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella Review of Text Message Programs for Adults With Type 2 Diabetes

Abstract: Purpose The purpose of this umbrella review was to synthesize the evidence from published systematic reviews on the effectiveness of text message programs for adults with type 2 diabetes (T2DM) on glycemic management (A1C), self-management, and other clinical outcomes. The effect of directionality of the program was also explored. Methods A systematic search was conducted using multiple databases. Inclusion criteria were systematic review of text message programs for adults with T2DM, evaluated A1C, and Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Important future research might investigate if the cost-effectiveness of DTEXT differed among different aged participants, culturally and linguistically diverse populations, those with differently controlled HbA1c or those with newly diagnosed type 2 diabetes as it is plausible that its effectiveness and costeffectiveness is heterogenous. For example, it is suggested that the early years of living with the disease is the optimal time to support behavior change and educational reinforcement (14), can provide greater treatment effects (14) and benefits to the individual and health system (35). Depending on its effectiveness and costeffectiveness in key population groups, implementation of DTEXT may be worth consideration in targeted populations as the simple and low cost delivery of automated text-messages can deliver ongoing support and provide an equitable adjunct to usual care.…”
Section: The Cost Of Delivering Dtext Intervention Was Low Atmentioning
confidence: 99%
See 2 more Smart Citations
“…Important future research might investigate if the cost-effectiveness of DTEXT differed among different aged participants, culturally and linguistically diverse populations, those with differently controlled HbA1c or those with newly diagnosed type 2 diabetes as it is plausible that its effectiveness and costeffectiveness is heterogenous. For example, it is suggested that the early years of living with the disease is the optimal time to support behavior change and educational reinforcement (14), can provide greater treatment effects (14) and benefits to the individual and health system (35). Depending on its effectiveness and costeffectiveness in key population groups, implementation of DTEXT may be worth consideration in targeted populations as the simple and low cost delivery of automated text-messages can deliver ongoing support and provide an equitable adjunct to usual care.…”
Section: The Cost Of Delivering Dtext Intervention Was Low Atmentioning
confidence: 99%
“…Text-message programs for people with type 2 diabetes have been shown to improve health outcomes and selfmanagement behaviors, are relatively inexpensive and provide a highly accessible mode of communication with the potential to address health disparities in diabetes care (14). A meta-analysis of 1,701 participants with type 2 diabetes receiving unidirectional text-messages showed a significant reduction in HbA1c of 0.38% (15), and a recent review on text-message programs for people with type 2 diabetes demonstrated a consistent moderate effect size on improvements in HbA1c (14). Despite this, text-message programs are an underutilized adjunct to clinical care (14), and there is no evidence on their cost-effectiveness or costs of scale-up to a population level in the Australian context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a trend was noted that less frequent messaging (weekly or biweekly) was associated with greater reductions in weight (mean −2.88 kg, 95% CI −4.56 to −1.21 kg) than for daily messages (mean −1.56 kg, 95% CI −2.26 to −0.86 kg), the authors concluded that the mechanisms of action by which SMS text messaging programs lead to these effects remain largely unclear, and further investigation into message delivery and content features is warranted. This is mirrored by other reviews that note the heterogeneity in message timing, frequency, and duration within the existing literature and call for future research to determine the optimal message dose for health behavior change [ 35 , 49 ].…”
Section: Introductionmentioning
confidence: 97%
“…Multiple umbrella reviews identify significant improvement in clinical outcomes, including hemoglobin A1C (A1C) when technology is part of the model of care. [1][2][3][4] These technologies include diabetes devices (eg, connected pens, glucose monitors and continuous glucose monitors), mobile devices (eg, mobile applications, wearables, fitness trackers) and technology-enabled communications (eg, text messaging, 2-way chat). In a 2017 review of high-quality systematic reviews, a framework evolved identifying 4 key elements of technology-enabled interventions associated with significant change in A1C.…”
Section: Introductionmentioning
confidence: 99%